2015
DOI: 10.1038/srep18157
|View full text |Cite
|
Sign up to set email alerts
|

Novel Iron-based ternary amorphous oxide semiconductor with very high transparency, electronic conductivity and mobility

Abstract: Here we report that ternary metal oxides of type (Me)2O3 with the primary metal (Me) constituent being Fe (66 atomic (at.) %) along with the two Lanthanide elements Tb (10 at.%) and Dy (24 at.%) can show excellent semiconducting transport properties. Thin films prepared by pulsed laser deposition at room temperature followed by ambient oxidation showed very high electronic conductivity (>5 × 104 S/m) and Hall mobility (>30 cm2/V-s). These films had an amorphous microstructure which was stable to at least 500 °… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 22 publications
2
8
0
Order By: Relevance
“…Optical properties. The optical characterization techniques utilized here were similar to those in our previous work 37 . Ultra-violet-Visible (UV-Vis) transmission spectra were obtained for all thin films deposited on quartz using an Ocean Optics spectrometer with a He-Ne light source that allowed measurements to be made between 300 nm to 900 nm, with integration time of 1 ms and 100 scans to average.…”
Section: • Transmission Electron Microscopy (Tem)mentioning
confidence: 99%
See 1 more Smart Citation
“…Optical properties. The optical characterization techniques utilized here were similar to those in our previous work 37 . Ultra-violet-Visible (UV-Vis) transmission spectra were obtained for all thin films deposited on quartz using an Ocean Optics spectrometer with a He-Ne light source that allowed measurements to be made between 300 nm to 900 nm, with integration time of 1 ms and 100 scans to average.…”
Section: • Transmission Electron Microscopy (Tem)mentioning
confidence: 99%
“…We note that in this regard, while a large number of crystalline oxide metals have been explored, amorphous oxides have not been that well studied. Recent reports have emerged of amorphous materials made from iron and lanthanide systems that appear to show promising electronic or magnetic behavior 37,38 and this forms the background for our studies.…”
mentioning
confidence: 99%
“…30 Recently, amorphous earth-abundant transition-metal oxides have been applied as a low-cost and highactivity cocatalyst materials. 31−33 Nevertheless, most techniques for their production, including electrodeposition, 34 pulsed laser deposition, 35 and plasma treatment, 36 have relatively complicated processing steps and high costs. As a result, MSD also emerges as an ideal fabrication route for amorphous OER cocatalysts since it provides a uniform distribution of the metal ions over the as-deposited amorphous film and can be feasibly extended to a large scale.…”
Section: Introductionmentioning
confidence: 99%
“…Van der Pauw sheet resistance and hall measurements were made following the NIST technique described in ref. 11 with the samples mounted on an Ecopia SPCB-1 board that allows contacts to be made via spring loaded gold pins.…”
Section: Methodsmentioning
confidence: 99%
“…Recently it was reported that oxide thin films made at room temperature by pulsed laser deposition from the metallic alloy, Terfenol-D, with composition of Fe (65.7 atomic %):Tb (10.3%):Dy (24%), showed an exciting combination of high transparency, very high Hall mobility, and a thermally stable amorphous microstructure 11 . As the authors showed, this material had a hall mobility μ H greater than 32 cm 2 /V-s, that is exceedingly high for an amorphous material (for instance amorphous Si has <1 cm 2 /V-s, while amorphous In-Ga-Zn-O ( α - IGZO ), which is presently being commercialized for use in electronic display devices, has μ H ~ 10 cm 2 /V-s) 4 8 .…”
mentioning
confidence: 99%